EFEKTIFITAS PENGGUNAAN MEDIA VIDEO UNTUK MENINGKATKAN PENGENALAN ALAT MUSIK DAERAH PADA PEMBELAJARAN IPS BAGI ANAK TUNAGRAHITA RINGAN DI SDLB 20 KOTA SOLOK - Putri - Nadya (Universitas Negeri Padang, 2012)
This study originated from the problems that researchers found in a social studies learning in class DIII / C SDLB 20 Solok City about the introduction of musical instruments, children are not familiar with musical instruments from the region. This study aims to improve the recognition of musical instruments using video media on learning for children of Social Sciences Tunagrahita lightweight class. This study uses a design approach Ekperiment Quasi-postes matching pretest control group design (control group design postest pratest-pairs). The subject of this study were all grade DIII / C at SDLB 20 Solok City numbering four. Data collection this study used the test as many as 10 pieces of advice about which was read orally, and the data obtained were analyzed using the Mann Whitney U test. The results of this study indicate that, Uhit = 1 and at a significant level of 95% or alpha = 0.05 is obtained Utab = 0 for n = 4. Based on the results of the testing criteria Uhit> Utab, accepted, meaning that Ha is received and Ho is rejected, it is proved that the use of video media is more effective in improving the recognition of musical instruments for children Tunagrahita lightweight class DIII / C SDLB 20 Solok City.